SAT0384 Patients that Continue to Flare Despite Reaching Eular/ ACR Recommended Serum Urate Target. (23rd January 2014) - Khanna, D.; Khanna, P. P.; Storgard, C.; Baumgartner, S.; Morlock, R.
Abstract : Background: Gout is a common inflammatory arthritis and its worldwide prevalence is increasing. EULAR and ACR Guidelines recommend a target serum urate (sUA) ≤ 6 mg/dL. For patients with significant crystal burden, sUA may need to be driven lower to reduce flares and decrease tophi as recommended by the ACR guidelines (2011). Objectives: To describe physician, patient and treatment characteristics in patients treated with xanthine oxidase inhibitor (XOI) therapy that achieve sUA ≤ 6 mg/dL yet have 2 or more physician confirmed gout flares per year. Methods: Data were assessed from a survey of US physicians about gout disease management. Patient results were confirmed through in-depth chart audits assessing diagnosis, comorbid conditions, disease severity and laboratory assessments. Disease severity was measured using a physician global assessment (mild, moderate or severe), flare counts, joint damage and presence of tophi. Type and dose of XOI, length of current treatment, compliance, physician type and patient socio-demographics factors were identified. Comorbidities were captured using chart review and analyzed as present or absent. Descriptive and multivariate statistics were used to describe patients having more than 2 flares per year (excluding treatment initiation flares) in patients achieving sUA ≤ 6 mg/dL. Results: 125 rheumatologists and 124 primary care physicians were interviewed. Of 1245 patients with gout, 81% were male and the average age was 57 (sd=13). 858 (69%) patients were treated with an XOI inhibitor[others were not treated (29%) or treated with non-XOI(2%)], of these 355 (42%) had a least one assessment sUA ≤ 6 mg/dL. Of the 355 patients reaching sUA target, 122 (34%) reported 2 or more flares in the last year. On average, patients with 2 or more physician confirmed flares were treated for 36.8 months on their current ULT and patients with 1 or no flares were treated for 37.2 months (p=0.9). Patients reporting 2 or more flares a year were more likely to have tophi (31% vs. 19%; p<0.01) compared to patients with 1 or less flare a year. A backward stepwise multivariate model predicting patients classified as controlled (sUA ≤ 6 mg/dL) and continuing to flare (2+ flares in the last year) found physician reported and chart documented co-existing comorbidities, chronic kidney disease (OR 2.7; p<0.01), alcoholism (OR 3.7; p<0.01), diabetes mellitus (OR 1.8; p<0.05) and hypertension (OR 1.7; p<0.05) to be associated with achieving sUA ≤ 6 mg/dL and higher flare rates. There was no difference by XOI or physician type. Results were similar for patients with a single sUA assessment ≤ 6mg/dL and patients with multiple sUA assessments ≤ 6 mg/dL during the study period. Conclusions: Less than 50% of patients treated with a XOI inhibitor alone reached sUA target. Of the patients achieving a sUA level of ≤ 6 mg/dL, over a third reported 2 or more flares in a 12-month period. Patients with multiple flares were more likely to have higher urate burden, chronic kidney disease and other comorbid conditions. Frequent flares and greater tophaceous burden may require treating to a sUA level of 5 mg/dL or lower as recommended by the ACR guidelines. Disclosure of Interest: D. Khanna Consultant for: Savient, Takeda and Ardea Biosciences, Speakers bureau: Savient, P. Khanna Speakers bureau: Takeda, C. Storgard Employee of: Ardea Biosciences, S. Baumgartner Employee of: Ardea Biosciences, R. Morlock Employee of: Ardea Biosciences